1988
DOI: 10.1021/bi00416a016
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effect studies of the pyridoxal 5'-phosphate dependent histidine decarboxylase from Morganella morganii

Abstract: The pyridoxal 5'-phosphate dependent histidine decarboxylase from Morganella morganii shows a nitrogen isotope effect k14/k15 = 0.9770 +/- 0.0021, a carbon isotope effect k12/k13 = 1.0308 +/- 0.0006, and a carbon isotope effect for L-[alpha-2H]histidine of 1.0333 +/- 0.0001 at pH 6.3, 37 degrees C. These results indicate that the overall decarboxylation rate is limited jointly by the rate of Schiff base interchange and by the rate of decarboxylation. Although the observed isotope effects are quite different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…This supports the hypothesis of Hare et al . that threonine ammonia‐lyase has an inverse isotope effect, and agrees with the inverse nitrogen equilibrium isotope effects of pyridoxal‐5'‐phosphate cofactor enzymes . While there is probably no single biochemical mechanism that can completely explain the bioaccumulation of 15 N in living organisms, we hypothesize that Schiff base formation between AAs and pyridoxal‐5'‐phosphate enzymes, notably during transamination, plays an integral role in the magnitude and variability of the nitrogen TLE.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This supports the hypothesis of Hare et al . that threonine ammonia‐lyase has an inverse isotope effect, and agrees with the inverse nitrogen equilibrium isotope effects of pyridoxal‐5'‐phosphate cofactor enzymes . While there is probably no single biochemical mechanism that can completely explain the bioaccumulation of 15 N in living organisms, we hypothesize that Schiff base formation between AAs and pyridoxal‐5'‐phosphate enzymes, notably during transamination, plays an integral role in the magnitude and variability of the nitrogen TLE.…”
Section: Discussionsupporting
confidence: 77%
“…[66] Pyridoxal-5'-phosphate enzymes are known for significant 15 N-equilibrium isotope effects as a result of Schiff base (aldimine) formation. In particular, Abell and O'Leary [67,68] found that glutamate decarboxylase (EC 4.1.1.15) and histidine decarboxylase (EC 4.1.1.22) have large inverse nitrogen equilibrium isotope effects that cause 15 N to be concentrated in the chemical bonds of Schiff bases. This is due to the reversible nature of these reactions, whereby 15 N-amino groups form stronger and more stable carbonnitrogen bonds than 14 N-amino groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence around PLP-binding lysine (Lys232) showed the conserved sequence Ser-X-His-(P-Pxy)-Lys earlier found in E. coli de carboxylases (32). The carbon and nitrogen isotope effects showed that the overall decarboxylation rate is jointly limited by the rate of transamination and by the intrinsic rate of decarboxylation (171), as is the case for glutamate decarboxylase. The carbon isotope effect of 1.05-1.06 on the decarboxylation step of HisDC is identical to that of GluDC (172), suggesting a similar transition state for the two enzymes.…”
Section: Histidine Decarboxylasementioning
confidence: 94%
“…The stereospeci®city of DDCs toward DAP results in inversion of the chiral center (Asada et al, 1981) and inversion may occur with the eukaryotic ODCs. This is in contrast to other bacterial decarboxylases, such as the bacterial ODC, glutamate and histidine decarboxylases, where retention of con®guration is conserved (Abell & O'Leary, 1988;Asada et al, 1984; crystallization papers Yamada & O'Leary, 1978). Here, we report the crystallization of a polyhistidine-tagged DDC from E. coli.…”
Section: Introductionmentioning
confidence: 86%